Histological Disease Activity as a Predictor of Clinical Relapse Among Patients With Ulcerative Colitis: Systematic Review and Meta‐Analysis. (December 2016) - Park, Sunhee; Abdi, Tsion; Gentry, Mark; Laine, Loren
Abstract : Objectives: Endoscopic remission in ulcerative colitis (UC) is associated with improved clinical outcomes. We assessed whether histological remission predicts clinical outcomes, estimated the magnitude of effect, and determined whether histological remission provides additional prognostic utility beyond clinical or endoscopic remission. Methods: Bibliographic databases were searched for studies in inflammatory bowel disease providing baseline histological status and relation to an outcome of clinical relapse or exacerbation. Our primary analysis compared the proportion of patients with study‐defined histological remission vs. the proportion with histological activity who developed clinical relapse/exacerbation. Additional analyses compared the proportion with relapse/exacerbation for the presence vs. absence of different histological features and for histological remission vs. endoscopic remission and clinical remission. A fixed‐effect model was used for meta‐analysis, with a random‐effects model if statistical heterogeneity was present. Results: Fifteen studies met inclusion criteria. The major methodological shortcoming was lack of blinding of the assessor of clinical relapse/exacerbation to baseline histological status in 13 of the 15 studies. Relapse/exacerbation was less frequent with baseline histological remission vs. histological activity (relative risk (RR)=0.48, 95% confidence interval (CI) 0.39–0.60) and vs. baseline clinical and endoscopic remission (RR=0.81, 95% CI 0.70–0.94). Relapse/exacerbation was also less common in the absence vs. presence of specific histological features: neutrophils in epithelium (RR=0.32, 95% CI 0.23–0.45), neutrophils in lamina propria (RR=0.43, 95% CI 0.32–0.59), crypt abscesses (RR=0.38, 95% CI 0.27–0.54), eosinophils in the lamina propria (RR=0.43, 95% CI 0.21–0.91), and chronic inflammatory cell infiltrate (RR=0.28, 95% CI 0.10–0.75). Histological remission was present in 964 (71%) of the 1360 patients with combined endoscopic and clinical remission at baseline. Conclusions: UC patients with histological remission have a significant 52% RR reduction in clinical relapse/exacerbation compared with those with histological activity. Histological remission is also superior to endoscopic and clinical remission in predicting clinical outcomes. As ˜30% of patients with endoscopic and clinical remission still have histological activity, addition of histological status as an end point in clinical trials or practice has the potential to improve clinical outcomes.